A comparison of performance and kinematics in throwing with the dominant and non-dominant arm in handball players - van den Tillaar, R.; Ettema, G. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to compare the differences in throwing performance and kinematics between throwing with the dominant and non-dominant arm in experienced handball players. Significant differences in throwing performance (accuracy and ball velocity) were found between the dominant and non-dominant arm. Maximal velocity of most joint movements was significantly different between the arms. However, timing of these maximal velocities did not change. The main cause of the decreased ball velocity was probably the decreased range of motion of the internal rotation of the shoulder. The lower ball velocity was compensated by the increased ball release height, which was caused by increased shoulder abduction and trunk tilt sideways angle at ball release.